Investigation of Embezzlement of Budget Funds: Efficiency Issues - A. V. Chumakov (Сибирское юридическое обозрение, 2024)
The paper analyzes scientific and theoretical, organizational and practical ideas about the effectiveness and inefficiency of the investigation of criminal cases in general, and cases of embezzlement of budgetary funds, in particular. Case studies of effective and ineffective investigation of the specified criminal activity are given. The definition of effectiveness is formulated in relation to the investigation of embezzlement of budgetary funds, in which compliance with the main priorities of the state policy of the Russian Federation is important. The paper analyzes the criteria for evaluating the law enforcement activities of law enforcement agencies. There are contradictions between the criteria of real effectiveness of the investigation and the requirements of statistical reporting by investigative authorities. In the context of the effective investigation criterion and with regard to the provisions of the “National Security Strategy of the Russian Federation” approved by the President of the Russian Federation, priorities of effective investigation in criminal cases of embezzlement of budgetary funds have been identified. This is a priority for crime prevention, the need to combat, first of all, the most socially dangerous types of embezzlement committed by public authorities and organizations with state participation, especially corruption concerning those involved in national projects and fulfilling state defense orders. Full compensation for the damage caused and an increase in the level of responsibility for suchlike criminal activity are also a priority. The paper concludes that an effective investigation is the observance of these priorities. They should concern practical, organizational and managerial, and scientific activities. The requirements of statistical reporting by law enforcement agencies need to be adapted to the criteria of the real effectiveness of the investigation of criminal cases. Forensic scholarly research has to be aimed at providing priorities for the investigation of embezzlement, to demonstrate the implementation of efficiency criteria through the case studies as recommendations.